Reduction of the Impact of Fertilization and Irrigation On Processes in the Nitrogen Cycle in Vegetable Fields with BMPs - Eve-Marie Cockx; Eric H. Simonne (EDIS)
The goals of this article are to (1) present the N cycle as it relates to crop production, (2) describe how fertilization and irrigation affect the processes within N cycle, and (3) explain how the proposed BMPs may help reduce the negative environmental impact of these cultural practices. This document is HS948, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2003.